Identification and Characterization of Novel CFTR Potentiators - Gees, Maarten; Musch, Sara; Van der Plas, Steven; Wesse, Anne-Sophie; Vandevelde, Ann; Verdonck, Katleen; Mammoliti, Oscar; Hwang, Tzyh-Chang; Sonck, Kathleen; Stouten, Pieter; Swensen, Andrew M.; Jans, Mia; et al. (Frontiers in Pharmacology, 2018)
There is still a high unmet need for the treatment of most patients with cystic fibrosis. The identification and development of new Cystic Fibrosis Transmembrane conductance Regulator (CFTR) modulators is necessary to achieve higher clinical benefit in patients. In this report we describe the characterization of novel potentiators. From a small screening campaign on F508del CFTR, hits were developed leading to the identification of pre-clinical candidates GLPG1837 & GLPG2451, each derived from a distinct chemical series. Both drug candidates enhance WT CFTR activity as well as low temperature or corrector rescued F508del CFTR, and are able to improve channel activity on a series of Class III, IV CFTR mutants. The observed activities in YFP halide assays translated well to primary cells derived from cystic fibrosis (CF) lungs when measured using TransEpithelial Clamp Circuit (TECC). Both potentiators improve F508del CFTR channel opening in a similar manner, increasing the open time and reducing the closed time of the channel. When evaluating the potentiators in a chronic setting on corrected F508del CFTR, no reduction of channel activity in presence of potentiator was observed. The current work identifies and characterizes novel CFTR potentiators GLPG1837 and GLPG2451, which may offer new therapeutic options for CF patients.